THE EFFECT OF ONLINE ACCOUNTING APPLICATIONS, ENTREPRENEURIAL COMPETENCIES, AND COMPENSATION ON THE PERFORMANCE OF BOOKKEEPERS IN MSMEs IN SEMARANG CITY - winarsih, Winarsih; Pamuji, Ratih Dewi (Universitas 17 Agustus 1945 Surabaya, 2024)
MSMEs have been proven to encourage national economic growth, as seen in MSME players who have the ability to prepare financial statements well and in accordance with financial accounting standards. The research aims to examine the effect of the benefits of online accounting applications, entrepreneurial competence, and compensation on bookkeepers in MSMEs in Semarang City. The research population was all MSMEs in Semarang City in 2020 – 2021. The sample used was 76 respondents. This research used primary data and secondary data in the form of performance assessments, attendance lists, and other supporting data that can be used to support primary data. Data were analyzed using Multiple Linear Regression Analysis. The research results show that online accounting applications, entrepreneurial competence, and compensation have a significant effect on bookkeeping performance in MSMEs in Semarang City. This has the implication that by using online accounting applications, entrepreneurial competencies, and good compensation, it is hoped that MSMEs will be able to make the right management decisions in improving good bookkeeping performance. Furthermore, good bookkeeping performance can be used to make appropriate decisions to increase business sustainability. With these findings, it is hoped that the government will support the development of MSMEs and that they can be managed well and in accordance with regulations set by the local government. Keywords: Online Accounting Application, Entrepreneurial Competencies, Compensation, Bookkeepers Performance